2020
DOI: 10.1177/0961000620966644
|View full text |Cite
|
Sign up to set email alerts
|

The effect of librarians’ digital skills on technology acceptance in academic libraries in Jordan

Abstract: Digital skills are necessary to work and manage electronic library infrastructures and services. Accordingly, there is an urgent need for assessing the level of digital skills among librarians at academic libraries in Jordan. It is also important to investigate the influence of digital skills on technology acceptance among librarians in Jordan. A questionnaire was developed and used to collect the required data from university libraries in Jordan. The results indicate a high level of digital skills among the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 26 publications
(43 reference statements)
4
17
0
Order By: Relevance
“…The integrated library system helps libraries to perform their various daily routine functions, technical process, record keeping, acquisition, cataloging, user management, circulation, statistical reporting, etc., efficiently and also eliminates delays (Bills, 2000;Congleton, 2002;Siddique & Mahmood, 2015;2016). Many researchers researched the use of modern technologies to automate library functions (Hamad, Al-Fadel & Fakhouri, 2021;Ahmed & Sheikh, 2021). A plenty of literature strengthens the results of the present study open-source software is a top choice of library professionals to select for library automation (Rafiq & Ameen, 2009;2010;Rehman, Mahmood & Bhatti, 2012;Siddique & Mahmood, 2015;Khan & Sheikh, 2022).…”
Section: Findings and Discussionsupporting
confidence: 70%
“…The integrated library system helps libraries to perform their various daily routine functions, technical process, record keeping, acquisition, cataloging, user management, circulation, statistical reporting, etc., efficiently and also eliminates delays (Bills, 2000;Congleton, 2002;Siddique & Mahmood, 2015;2016). Many researchers researched the use of modern technologies to automate library functions (Hamad, Al-Fadel & Fakhouri, 2021;Ahmed & Sheikh, 2021). A plenty of literature strengthens the results of the present study open-source software is a top choice of library professionals to select for library automation (Rafiq & Ameen, 2009;2010;Rehman, Mahmood & Bhatti, 2012;Siddique & Mahmood, 2015;Khan & Sheikh, 2022).…”
Section: Findings and Discussionsupporting
confidence: 70%
“…The results are in line with Okeji et al (2019), who investigated digital literacy skills and revealed that Nigerian librarians are not very knowledgeable on computer networking, software coding and system security protection and digital content protection and the creation of different file formats. Findings also support Hamad et al (2021), who revealed that academic library professions were not very vast on advanced levels of digital literacy skills such as coding, library website development, cloud computing, big data and database designs. To ensure effective use and management of digital technologies, these advanced skills are to be acquired by the African librarians.…”
Section: Discussion Of Findingssupporting
confidence: 68%
“…Previous studies found that information literacy was an important predictor of students’ academic emotions (Lee & Lee, 2021a ; Hamad et al, 2021 ; Blažič & Blažič, 2020 ). For example, Guo et al ( 2015 ) found that information-literate individuals could effectively find, evaluate, seek, filter, and use information.…”
Section: Theoretical Frameworkmentioning
confidence: 93%